O arrojo do Comité Europeu dos Direitos Sociais na tutela da segurança e saúde no trabalho - Costa, Ana Cristina Ribeiro (2017)
Occupational health and safety is directly foreseen by the art. 3 of the European Social Charter (ESC), even though it is also indirectly covered by other norms that regulate the right to just working conditions, protect children and young persons’ work, maternity of employed women and health, and assure the workers’ involvement in the fixing and improving of the working conditions and environment, and determine the right to dignity at work – articles 2 (4), 7, 8, 11, 22 (b) and 26 of the ESC. These norms have been interpreted in a constructive and dignifying way by the European Committee of Social Rights, through the issuing of conclusions subsequent to the reports presented by the States that signed the Charter, as well as through the decisions reported under the collective complaints’ system.